The Error in an Alternating Series - Villarino Bertram, Mark (2018)
We present a new proof of Johnsonbaugh’s estimates for the error in an alternating series based on an idea of R. M. Young. We also use this same idea to prove the convergence of the Euler transform and a corresponding error estimate.